INHIBISI KOROSI OLEH HIDROKSILAMIN NETRAL SULFAT TERMODIFIKASI TERHADAP BAJA KARBON - (The Corrosion Inhibition by Modified Hydroxylamine Neutral Sulfate on Carbon Steel) - Vachlepi, Afrizal; Suwardin, Didin (Biopropal Industri, 2016)
Production of natural rubber SIR 20CV requires Hydroxylamine Neutral Sulfate (HNS) as stabilizing agent which serves to stabilize viscosity of natural rubber. Several methods of HNS applications among others are spraying, soaking and mixing into the latex. The HNS use may cause corrosion of processing equipments. The aims of this research were to explore the charateristics of modified HNS as stabilizing agents to reduce the corrosion attack on carbon steel. Treatments were consisted of pure HNS and modified HNS. The method was weight loss method with planned interval test. Removal of corrosion products on metal specimen was done by chemical cleaning method based on ASTM G1-90. The results showed that weight loss percentage and corrosion rate of carbon steel by modified HNS were lower than pure HNS. Corrosion resistance criteria of carbon steel by modified HNS was classified as outstanding. Inhibition efficiency of corrosion by modified HNS reached around 98-99%.Keywords: corrosion, inhibition, modified HNS, natural rubberÂ ABSTRAKProduksi karet alam SIR 20CV memerlukan hidroksilamine netral sulfat (HNS) sebagai bahan pemantap yang berfungsi menjaga viskositas karet alam stabil. Beberapa metode aplikasi HNS antara lain penyemprotan, perendaman dan pencampuran ke dalam lateks. Penggunaan HNS dapat menyebabkan korosi pada peralatan pengolahan. Tujuan penelitian ini adalah untuk mempelajari dan mengetahui karakteristik inhibisi bahan pemantap HNS termodifikasi dalam mengurangi serangan korosi terhadap logam baja. Perlakuan yang diberikan terdiri atas HNS murni dan HNS termodifikasi. Metode yang digunakan adalah metode kehilangan berat dengan planned interval test. Penghilangan produk korosi pada spesimen logam baja karbon dilakukan dengan metode pembersihan kimia berdasarkan ASTM G1-90. Hasil penelitian menunjukkan bahwa persentase kehilangan berat dan laju korosi baja karbon oleh HNS termodifikasi lebih rendah dibandingkan HNS murni. Kriteria ketahanan korosi logam baja karbon oleh HNS termodifikasi tergolong luar biasa. Efisiensi inhibisi serangan korosi oleh HNS termodifikasi mencapai sekitar 98-99%.Kata kunci: HNS termodifikasi, inhibisi, karet alam, korosi